MEMPERCEPAT KONEKSI AKSES INTERNET DENGAN MEMBANGUN LUSCA PROXY SERVER MENGGUNAKAN LINUX PFSENSE PADA UNIVERSITAS MUHAMMADIYAH METRO - Dedi Irawan (IIB Darmajaya, 2012)
Metro is a college of University of Muhammadiyah Muhammadiyah tingggi domiciled in the City Metro Lampung Province, including work areas Kopertis II Palembang. The current condition of Muhammadiyah University of Metro has 5 faculties and 18 courses. The bandwidth owned by the University of Muhammadiyah Metro is currently at 2 Mbps is used to serve the needs internet access at 5 faculties and 18 courses. Muhammadiyah University of Metro seeks to improve the quality of learning that is excellent service by using information technology which is using the Youtube site. From the results of research testing LUSCA Proxy Server, the time it takes the Internet network standard can be summed up as follows: (a) The absence of the network design and the absence LUSCA Internet Proxy Server at the University of Muhammadiyah Metro is causing Internet access to be slow so it takes Plan LUSCA Proxy Server to increase the speed of internet access. (b) Based on the results of this study concluded LUSCA Proxy Server is a technology solution to speed up Internet access, especially access youtube site at the University of Muhammadiyah Metro. (c) Based on calculations before and after the Proxy Server installed LUSCA obtained an average time difference between before and after the implementation of LUSCA Proxy Server for 232.2 seconds and the average time efficiency between before and after the implementation of the Proxy Server LUSCA 97.16 %.Keywords: LUSCA, proxy, server, youtube, youtube cache, refresh_pattern, storeurl.pl, hit content.